How television moved a nation: media, change and Indigenous rights - Lisa Waller; Kerry McCallum (2018)
This article examines the role of television in Australia’s 1967 referendum, which is widely believed to have given rights to Aboriginal and Torres Strait Islander peoples. It presents an analysis of archival television footage to identify five stories that moved the nation: Australia’s shame, civil rights and global connections, admirable activists, ‘a fair go’ and consensus. It argues that television shaped the wider culture and opened a channel of communication that allowed Indigenous activists and everyday people to speak directly to non-Indigenous people and other First Nations people throughout the land for the first time. The referendum narrative that television did so much to craft and promote marks the shift from an older form of settler nationalism that simply excluded Indigenous people, to an ongoing project that seeks to recognise, respect and ‘reaccredit’ the nation-state through incorporation of Indigenous narratives. We conclude that whereas television is understood to have ‘united’ the nation in 1967, 50 years later seismic shifts in media and society have made the quest for further constitutional reform on Indigenous rights and recognition more sophisticated, diffuse, complex and challenging.